Risking a somersault in the air : conversations with Nicaraguan writers - Randall, Margaret, 1936- (New Village Press, 2022)
"First revised edition of interviews with 14 prominent activists whose writings influenced the 1979 Nicaraguan revolution and help us understand present-day Nicaragua. Margaret Randall presents a dynamic collection of personal interviews with Nicaragua's most important writer-revolutionaries who played major roles in the 1979 revolution and the subsequent reconstruction. This revised first edition includes a new preface and additional notes that frame the narrative in high relevance to the present day. The featured writer-activists speak of their work and practical tasks in constructing a new society. Among the writers included are Gioconda Belli, Tomás Borge, Omar Cabezas, Ernesto Cardenal, Vidaluz Menéses, Julio Valle-Castillo, and Daisy Zamora. The work also features 50 evocative photographs from the era by Margaret Randall"--